التحري عن وجود جراثيم الكلِبْسيلَّة من بعض أنواع التوابل المأخوذة من الأسواق المحلية (Latakia University Journal -Biological Sciences Series, 2013)
للتوابل أهمية آخذة في الازدياد نظراً إلى احتوائها على عناصر فعالة وكونها تُستعمل كصادات حيوية،  وفي الوقت الحاضر يتجه العالم نحو استعمال بعض التوابل بدلاً من الأدوية الكيماوية، إلا أن ذلك لا يعني خلوها من عوامل ممرضة قد تكون خطيرة ومنها جراثيم  الكلِبْسيلَّة  Klebsiella spp. التي يمكن أن تُسبب العديد من الحالات المرضية، ولاسيَّما الالتهاب الرئوي، إنتانات المسالك البولية، وتجرثم الدم. وبالرغم من أن الموطن الطبيعي للكلِبْسيلَّة غير محدد بدقة إلا أنَّ وجودها بنسبة كبيرة في التوابل قد يشير إلى أن النباتات تمثل الخازن الطبيعي لها. أُجري العزل الأولي للكلِبْسيلَّة بتنميتها على وسط منمي عام، ثمَّ على وسط اصطفائي، إن مستعمرات الكلِبْسيلَّة المعزولة دائرية محدبة قطرها 3-4 مم، ذات حواف مخاطية ولزجة، وتكون محاطة بمحفظة. وأمكن تحديد هويتها من خلال التفاعل السلسلي للبوليميراز PCR، والاختبارات الحيوية الكيميائية. وقد أظهرت النتائج أن نحو 32% من العينات المدروسة تحتوي جراثيم الكلِبْسيلَّة. Spices are becoming increasingly important world-wide due to their effectiveness as natural antibiotics, the thing that makes the world nowadays tend to use spices instead of chemical drugs. However, this doesn’t mean they are free of some dangerous pathogens such as Klebsiella spp. which can lead to a wide range of illnesses, notably pneumonia, urinary tract infections (UTIs), and bacteremia. Although we don’t know the natural habitat of this bacterium we find that it thrives in herbs and spices, concluding thus that plants may be its natural habitat. The primary isolation of this bacterium was based first on its growth on general media and then isolation on selective media. Colonies of the microorganisms were counted on different media then Klebsiella was isolated from a selective media. The isolated colonies of Klebsiella were circular, dome-shaped, 3-4 mm in diameter, with mucoid sticky edges, and surrounded by capsule. After this we chose the typical colony and identified it using Polymerase chain reaction PCR and biochemical tests. Our results showed that 32% of examined specimen contained Klebsiella spp.